(8x -3)(3x+2) – (4x+7)(x+4) = 2(2x+1)(5x-1) Tìm x, giải chi tiết nhùm mk

(8x -3)(3x+2) – (4x+7)(x+4) = 2(2x+1)(5x-1)
Tìm x, giải chi tiết nhùm mk

0 bình luận về “(8x -3)(3x+2) – (4x+7)(x+4) = 2(2x+1)(5x-1) Tìm x, giải chi tiết nhùm mk”

  1. Đáp án:

    $ (8x-3)(3x+2) – (4x+7)(x+4) = 2(2x+1)(5x-1)$

    $⇔ 24x² +15x -9x -6 -4x² -15x -7x -28 = 20x² -4x +10x -2 $

    $⇔ 24x² -4x² -20x² +15x -9x -15x -7x -10x +4x = -2 +28+6$

    $⇔ -22x = 32$

    $⇔x=32 : (-22)$

    $⇔ x = -\dfrac{16}{11}$

    $\text{Vậy x= -$\dfrac{16}{11}$}$

     

    Bình luận
  2. (8x – 3)(3x + 2) – (4x + 7)(x + 4) = 2(2x + 1)(5x – 1)

    ⇔ 24x² + 16x – 9x – 6 – (4x² + 16x + 7x + 28) = (4x + 2)(5x – 1)

    ⇔ 24x² + 16x – 9x – 6 – 4x² – 16x – 7x – 28 = 20x² – 4x + 10x – 2

    ⇔ 24x² + 16x – 9x – 4x² – 16x – 7x – 20x² + 4x – 10x = – 2 + 6 + 28

    ⇔ -22x = 32

    ⇔       x = -32/22

    ⇔       x = -16/11

    Vậy pt có tập nghiệm: S = {-16/11}

    Bình luận

Viết một bình luận